EFFECT OF MINERAL NUTRITION ON NUT YIELD AND FRUIT COMPOSITION OF MATURE COCONUT PALMS IN THE COASTAL BELT OF WESTERN REGION OF GHANA - PRELIMINARY STUDIES - E. Andoh-Mensah; X. Bonneau; B.N. Nuertey; S.K. Dery (International Coconut Community Journal, 2003)
The nut yield and fruit composition of mature (30-40 years old) West African Tall coconut palms were evaluated in seven trials during the first three years (from June 2000 to May 2003) of implementation of a five-year fertilization schedule recommended to the Coconut Sector Development Project (CSDP) for the rehabilitation of old farms in the coastal belt of the Western Region of Ghana. The seven trials are located at Jeway Wharf, Takinta, Ellenda, Nawule, AB Bokazo, Anwia and Edwakpole. Three fertilizer treatments were applied between June 2000 and May 2003. The first two fertilizers were applied in June 2000 and May 2001 at the rate of 0.75kg urea and 2.5kg muriate of potash (MOP) per palm. For the third fertilization, 1 kg MOP only was applied per palm in May 2002. Fertilizer treatment did not affect nut yield in year one of fertilization. But in year two, the fertilized plots gained remarkably 27.7, 20.2, 19.4 and 14.9 nuts per palm at Jeway Wharf, Nawule, Ellenda and Takinta respectively. The remarkable nut gain was further boosted or sustained in year three except at Jeway wharf which lost 9.8 nuts per palm. In economic terms, Ellenda trial broke even on MOP fertilizer investment in year three while Jeway Wharf was close to breaking even. Takinta and Nawule trials made profits of 925 and 1,750 cedis (3.7 and 7 nuts) per palm respectively in year three. For Anwia, AB Bokazo and Edwakpole trials there was no yield response to MOP fertilizer due to P deficiency. Fertilizer treatment in the first two years of fertilization did not influence fruit composition.